Mathematical modeling and identification of the mathematical model parameters of diesel fuel injection systems - Štavljanin, Miloljub S. (Vojnotehnički glasnik / Military Technical Courier, 2016)
The aim of the paperis to highlight, if not all, then at least the most important benefits of the application of mathematical modeling in the development of a new solution or in the process of improvement and the optimization of an existing product. The thesis presents the basic principles of the model creation without providing a detailed mathematical interpretation of the process; therefore, the model includes a substantial number of unknown or approximately known parameters and it is not possible to create a model of the transparent cybernetic box type. In order to achieve a synthesis of the model and the experimental results, it is necessary to apply the optimization methods for the identification of unknown model parameters. The thesis presents the experimental results along with the results of modeling and identification as well as the analysis of the process of identification of unknown model parameters.
Keywords: diesel engine; fuel injection system; mathematical modeling; identification